Farmer-Managed Natural Regeneration contribution to soil health in the southern part of Niger - Traore, Bouba; Arzika, Zaharadine L.; Koudoussou, Ibrahim M.; Desta, Gizaw; Moyo, Martin (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Farmer-Managed Natural Regeneration (FMNR) is more than a greening initiative—it is a critical intervention for soil health and climate resilience. Comparing Magaria’s landscape between 2019 and 2024 reveals a dramatic recovery. In 2019, half the department faced severe soil exposure due to low vegetation cover; by 2024, FMNR practices helped move 60% of the land into a healthy, productive state. The data shows that FMNR provides a "biological floor" that protects the land even during drought. By fostering indigenous tree growth, FMNR prevents erosion, manages floodwaters through better soil infiltration, and ensures a steady supply of nutrients. This restoration follows a non-linear path: as cover increases toward the 80% mark, the ecosystem reaches a tipping point where soil health becomes permanent and self-replenishing.